COLLABORATION ON RESEARCH METHODOLOGY TRAINING THROUGH VISITING MALAYSIAN PROFESSORS FOR LECTURERS IN INDONESIA - Yahya, Wachid; Sari, Anditha; Shidiq, Muhammad Agus; Burhanudin, Burhanudin; Muhamad, Wan Mansor Wan (Politeknik Indonusa Surakarta, 2024)
Improving the quality of research and development in the manufacturing industry is the main focus in the community service entitled